التمكين السياسي للمرأة الجزائرية بين الواقع والرهانات - عدان, نبيلة (جامعة الوادي University of Eloued, 2019)
لقد كانت ولا تزال دراسة المجتمع القضية المحورية في سلم اهتمامات الباحثين والممارسين خصوصا تلك الملفات المركزة على قضايا المرأة، نتيجة تنامي الأصوات الدولية والإقليمية المنادية بضرورة القضاء على فجوة اللامساواة بين الجندر(النوع الاجتماعي)، وعلى كل أشكال التمييز ضد المرأة باعتبارها شريكا أساسيا مكملا لمسارات التغيير والتنمية في المجتمعات الحديثة. تسعى هذه الدراسة لتناول التجربة الجزائرية في مجال التمكين السياسي للمرأة كونها من الدول التي نادت مرارا بأهمية إنصاف المرأة، وتفعيل مشاركتها في العملية السياسية وتعزيز فرص تواجدها في المجالس المنتخبة، وهذا الطرح لطالما تكرس في دساتيرها و بدا جليا من خلال القانون العضوي 12/03 المتضمن نظام الحصص أو ما يعرف بنظام "الكوتا" النسائية . The study of society has been the central issue in the field of researchers interests and practitioners, especially those who focused on women's issues, as a result of growing international and regional voices calling for the elimination of gender inequality, and all forms of discrimination against women who are considered as a key partner in the path of change and development in modern societies . This study seeks to present the Algerian experience in the field of women's political empowerment as one of the countries that has repeatedly called for the importance of women's equality, enhancing their participation in the political process and increasing their chances of being in elected councils. This proposal has always been enshrined in all constitutions, and reinforced by the quota system for woman in the organic law 12/03.
The Political Empowerment Of Algerian Women Between Reality And Challenges
Keywords: النوع الاجتماعي، ; المشاركة السياسية، ; تمكين المرأة سياسيا، ; نظام الحصص، ; الجزائر; Gender; Political Participation ; Woman’s Political Empowerment ; Quota System; Algeria